SOME RESULTS AND PROSPECTS OF NATIONAL RESEARCH UNIVERSITIES’ ACTIVITIES - Vasily M. Zhurakovsky (Высшее образование в России)
The article sums up the results of the activities of national research universities, gives anassessment of their effectiveness according to the main evaluation indexes: improvement of education process, development of research and innovation activities, development of human resources, research and pedagogical personnel, infrastructure changes, modernization of management systems, intensification of international communication. The analysis has been made on a basis of reports on universities’ development programs realization in 2012. The paper explores contribution of national research universities in development of industry areas, regions and territories, and the system of vocational education. There are revealed some problems in universities’ development and given the main guidelines on raising the effectiveness of universities’ development programs realization.